Prognostic value of tumour volume in patients with a poor Karnofsky performance status scale – a bicentric retrospective study - Barz, Melanie; Gerhardt, Julia; Bette, Stefanie; Aftahy, A. Kaywan; Huber, Thomas; Combs, Stephanie E.; Ryang, Yu-Mi; Wiestler, Benedikt; Skardelly, Marco; Gepfner-Tuma, Irina; Behling, Felix; Schmidt-Graf, Friederike; et al. (BMC Neurology, 2021)
Backround: Median overall survival (OS) after diagnosis of glioblastoma (GBM) remains 15 months amongst patients receiving aggressive surgical resection, chemotherapy and irradiation. Treatment of patients with a poor preoperative Karnofsky Performance Status Scale (KPSS) is still controversial. Therefore, we retrospectively assessed the outcome after surgical treatment in patients with a KPSS of ≤60%. Methods: We retrospectively included patients with a de-novo glioblastoma WHO °IV and preoperative KPSS ≤60%, who underwent surgery at two neurosurgical centres between September 2006 and March 2016. We recorded pre- and postoperative tumour volume, pre- and postoperative KPSS, OS, age and MGMT promoter status. Results: One hundred twenty-three patients (58 females/65 males, mean age 67.4 ± 13.4 years) met the inclusion criteria. Seventy-five of the 123 patients (61%) underwent surgical resection. 48/123 patients (39%) received a biopsy. The median preoperative and postoperative tumour volume of all patients was 33.0 ± 31.3 cm3 (IR 15.0–56.5cm3) and 3.1 ± 23.8 cm3 (IR 0.2–15.0 cm3), respectively. The median KPSS was 60% (range 20–60%) preoperatively and 50% (range 0–80%) postoperatively. Patients who received a biopsy showed a median OS for patients who received a biopsy only was 3.0 months (95% CI 2.0–4.0 months), compared to patients who had a resection and had a median OS of 8 months (95% CI 3.1–12.9 months). Age (p < 0.001, HR: 1.045 [95% CI 1.022–1.068]), postoperative tumour volume (p = 0.02, HR: 1.016 [95% CI 1.002–1.029]) and MGMT promotor status (p = 0.016, HR: 0.473 [95% CI 0.257–0.871]) were statistically significant in multivariate analysis. In subgroup analyses only age was shown as a significant prognostic factor in multivariate analyses for patients receiving surgery (p < 0.001, HR: 1.046 [95% CI 1.022–1.072]). In the biopsy group no significant prognostic factors were shown in multivariate analysis. Conclusion: GBM patients with a preoperative KPSS of ≤60% might profit from surgical reduction of tumour burden.
CRIS-Team Scopus Importer:2023-03-08
Keywords: EOR; Glioblastoma; Karnofsky performance status scale; Surgery